On the release of cppxfel for processing X‐ray free‐electron laser images. Issue 3 (11th May 2016) - Ginn, Helen Mary; Evans, Gwyndaf; Sauter, Nicholas K.; Stuart, David Ian
Abstract : Here cppxfel, a software package for integration and post‐refinement of serial femtosecond crystallography data, is released. Abstract : As serial femtosecond crystallography expands towards a variety of delivery methods, including chip‐based methods, and smaller collected data sets, the requirement to optimize the data analysis to produce maximum structure quality is becoming increasingly pressing. Here cppxfel, a software package primarily written in C++, which showcases several data analysis techniques, is released. This software package presently indexes images using DIALS (diffraction integration for advanced light sources) and performs an initial orientation matrix refinement, followed by post‐refinement of individual images against a reference data set. Cppxfel is released with the hope that the unique and useful elements of this package can be repurposed for existing software packages. However, as released, it produces high‐quality crystal structures and is therefore likely to be also useful to experienced users of X‐ray free‐electron laser (XFEL) software who wish to maximize the information extracted from a limited number of XFEL images.